Issues in Teaching Translation - Petro, Jonida (Richtmann Publishing, 2012)
The present article aims initially to present some major theoretical reflections about the translational process and the manyvarious approaches when it comes to the texts to be translated. Then it elaborates on a subsequent teaching procedure carried out withundergraduate translation students. The methodology of this article, consists of a step-by-step, either sequential or successiveprocedure for workshops, has proven quite successful in translator training at an undergraduate level. The educator is understood as afacilitator of the translation task: The article underlines that the nature of the lesson is quite cooperative and tackles concepts such as theprofile of the educator, that of the student, the necessary infrastructure for the teaching and learning processes as well the assessmentprocess. Most of the transfer process is carried out by the students both collectively and individually. The article elaborates such aspectsas Influence of the mother tongue, naturalness of the activity, the skill aspect, the reality of language. In conclusion after themethodology proposed and the relevant processes are discussed, the article will conclude with the idea that translators—as every“professional